2011
DOI: 10.5455/cap.20110320
|View full text |Cite
|
Sign up to set email alerts
|

Emotion and Autobiographical Memory

Abstract: Benlik ve zihin, insanın anlamlı geçmiş yaşantılarının birikimli etkisi ile oluşur. Bu tanım örtük ya da açık olarak pek çok kişilik kuramının temel kabulüdür. Böyle bir kabul hangi yönelimden olursa olsun kişilik kuramlarını kaçınılmaz olarak iki temel kavram üzerinde buluşturur. Bunlardan ilki yaşan-tılara anlam veren duygular, ikincisi ise bu yaşantıların birikimli şekilde saklanmasıyla ilgili olarak bellektir. Yaşantıların saklandığı ve geri getirildiği bellek yapısı otobiyografik bellektir. Kişilik oluşum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
(90 reference statements)
0
4
0
2
Order By: Relevance
“…The model aims to re-evaluate and functionally address the memories processed into verbally accessible memory while working with the cognitions of trauma victims and to activate the information processed into situationally accessible memory by confronting them with the necessary stimuli and updating them within functional new moods (Brewin et al 1996, Karancı 2009, Sarp and Tosun 2011. 2010) express their cognitive model of trauma as a hybrid of the models explained by Foa and Kozak (1986), Ehlers and Clark (2000), and Brewin et al (1996).…”
Section: Dual Representation Theorymentioning
confidence: 99%
“…The model aims to re-evaluate and functionally address the memories processed into verbally accessible memory while working with the cognitions of trauma victims and to activate the information processed into situationally accessible memory by confronting them with the necessary stimuli and updating them within functional new moods (Brewin et al 1996, Karancı 2009, Sarp and Tosun 2011. 2010) express their cognitive model of trauma as a hybrid of the models explained by Foa and Kozak (1986), Ehlers and Clark (2000), and Brewin et al (1996).…”
Section: Dual Representation Theorymentioning
confidence: 99%
“…In the last few years, the schema therapy model (STM) and autobiographical memories have been studied with increasing interest as two unrelated topics of psychology. The lack of connection might be explained when we consider that memory models emphasize cognitive structures, while clinical approaches tend to ignore memory processes (1). At the same time, the STM studies autobiographical memories of early negative experiences by establishing a link between past and present.…”
Section: Introductionmentioning
confidence: 99%
“…The emotions that constitute a context for the recall of autobiographical memories play an important role in the autobiographical memory characteristics (21). Emotions occuring during experiences affect how that experience is encoded into memory, how it is stored and how it is recalled under what conditions (1). From this perspective, autobiographical memories are closely related to emotions (5,15,22).…”
Section: Introductionmentioning
confidence: 99%
“…Research converges on the idea that the ways in which people reflect on their pasts can inform psychological well‐being for better (e.g., greater perceived social support; Zhou, Sedikides, Wildschut, & Gao, 2008) or worse (e.g., heightened reliving of distress; Reynolds & Brewin, 1999). Prior studies have demonstrated that different ways of construing events can influence judgments about the self, others, and the future (Libby & Eibach, 2011b); identity and life‐story significance (McAdams, 2001); sense of closure (Crawley, 2010); emotion regulation (Cox & McAdams, 2014); goal pursuit (Conway, Singer, & Tagini, 2004); and psychopathology (Sarp & Tosun, 2011). It is therefore important to identify effective strategies for representing autobiographical events, along with possible mechanisms that promote adaptive self‐reflection.…”
mentioning
confidence: 99%